1994
DOI: 10.1172/jci117239
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 attenuates agonist-mediated calcium mobilization in murine osteoblastic cells.

Abstract: Interleukin-6 (IL-6) is a multifunctional cytokine which is made by osteoblasts and has diverse effects on bone metabolism. We studied the interaction of IL-6 with the Ca2" and cAMP signaling systems in the osteoblastic cell line UMR-106 and in primary osteoblastic cultures derived from neonatal rat calvariae. IL-6 did not alter basal intracellular calcium concentration (ICa2+J1) but inhibited Ca2+ transients induced by parathyroid hormone (PTH), prostaglandin E2 (PGE2), and endothelin-1 in both dose-(100-400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 62 publications
0
16
1
Order By: Relevance
“…In fact, IL-1␤, together with TNF␣, induces the release of tissue-damaging enzymes from synovial cells and articular chondrocytes and activates osteoclasts (30,31). IL-6 participates together with IL-1 in the catabolism of connective tissue components at inflammation sites (32,33), and activates osteoclasts, resulting in joint destruction (34). It is likely that a decrease in IL-6 and IL-1␤ is one of the factors involved in the amelioration of articular lesions upon anti-IL-18 treatment in our experimental model.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, IL-1␤, together with TNF␣, induces the release of tissue-damaging enzymes from synovial cells and articular chondrocytes and activates osteoclasts (30,31). IL-6 participates together with IL-1 in the catabolism of connective tissue components at inflammation sites (32,33), and activates osteoclasts, resulting in joint destruction (34). It is likely that a decrease in IL-6 and IL-1␤ is one of the factors involved in the amelioration of articular lesions upon anti-IL-18 treatment in our experimental model.…”
Section: Discussionmentioning
confidence: 92%
“…In fact, TNF-␣ and IL-1␤ are known to contribute directly to tissue damage through induction of the release of tissue-damaging enzymes from synovial cells and articular chondrocytes and through activation of osteoclasts (2,47,53). Moreover, IL-6 participates together with IL-1 in catabolism of connective tissue components at sites of inflammation (25,36) and activates osteoclasts, with a consequent increase in joint damage (19). The early exacerbated inflammatory response caused by IL-10 neutralization could also account for the increase in mortality rates observed in the anti-IL-10-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no direct evidence for an arthritogenic role of IL-6, we have recently shown that IL-6 knock-out mice developed less arthritis as compared to the healthy littermates after injection with the arthritogenic LS-1 strain (Hultgren, in preparation). Furthermore, it has been demonstrated recently that this cytokine acts on haematopoietic progenitors to recruit osteoclasts thereby stimulating bone resorption [26]. In parallel, overexpression of the TNF gene, which is encoded within the MHC locus [1] and whose product is known to be of pathogenic significance in septic arthritis [27], might contribute to the increased morbidity in S. aureus arthritis.…”
Section: Discussionmentioning
confidence: 99%